ANALISIS PERAN MANAGERIAL OWNERSHIP DAN INTELLECTUAL CAPITAL TERHADAP FIRM VALUE - DEVIN DHAMMATTHA; NOVIA WIJAYA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This research was conducted to obtain empirical evidence regarding the influence of managerial ownership, intellectual capital, and other factors on firm value. In this research, there are seven independent variables, namely managerial ownership, intellectual capital, profitability, capital structure, liquidity, firm size, and tax avoidance. This study uses 345 firm-year observations from 115 manufacturing companies listed on the Indonesia Stock Exchange during 2022 -2024. The study employs a purposive sampling method in selecting the sample and uses multiple regression analysis in conducting data analysis. The results of this study indicate that profitability, capital structure, and firm size significantly affect firm value. However, other independent variables such as managerial ownership, intellectual capital, liquidity, and tax avoidance do not have an effect on firm value.